PENGEMBANGAN SUMBER DAYA MANUSIA (SDM) DALAM PENINGKATAN PRODUKTIFITAS DI LEMBAGA PENDIDIKAN - Muli Prima Aldi (STAI Nurul Falah Airmolek, 2023)
The better the education of a nation, the better the quality of a country, which is a general assumption regarding a nation's education program. In fact, education describes the group activities of a group of teachers and other educational personnel carrying out education in collaboration with interested people. In essence, education has the principles of movement in matter, interaction, innovation and ideals. Education in the individual's view is the cultivation of the wealth or potential that exists in each individual so that it is useful for the individual himself and can be presented to society. Meanwhile, in the community's view, it is the inheritance of culture and the development of potential. The above illustrates that advanced education is supported by good and superior resources, both planning, management and development of human resources in educational organizations. Management of organizational human resources is very dependent on the quality of the people in it, organizational leadership is the starting point of change where a pattern of leader behavior attempts to influence others to achieve the goals set in education.